Musykilah At-Thulab fi Ta'alum Al-Lughah Al-Arabiyah Li al-Fashl At-Tahdiri bi Jamiah Darussalam Gontor / Student Problems in Learning Arabic In the Matriculation Class at Darussalam Gontor University - Yoke Suryadarma; Moh. Ismail; Muhammad FahrulRozi (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
This research aims to analyze student problems in learning Arabic in Arabic matriculation class at Darussalam Gontor University, Siman Campus in the 2022-2023 academic year. The result of this research is that two basic problems were founded in student’s problems in learning Arabic in the matriculation class, are linguistic problems such as a) lack of student understanding of the lessons that have been delivered by the teacher, b) lack of student’s writing on Arabic, c) lack of student’s memorization on Arabic vocabulary. And non-linguistic problems such: as a) lack of student motivation in learning Arabic, b) The decrease in Arabic-language textbooks among students, etc. Based on the results of the study, the researcher suggests that the parties involved with students, especially Arabic language teachers, pay attention to the seriousness of student learning and give them continuous motivation in learning Arabic so that they are motivated to continue learning Arabic and able to communicate with it in their daily lives. This research naturally made a high contribution to spreading the knowledge that there are problems in learning Arabic from the student’s side that are not only linguistic but also non-linguistic.المستخلص: يهدف هذا البحث إلى تحليل مشكلات الطلاب في تعلم اللغة العربية في الفصل التحضيري بجامعة دار السلام، الحرم سيمان، في العام الدراسي 2022-2023. وتوصلت نتيجة هذا البحث إلى وجود مشكلتين أساسيتين في مشكلات الطلاب في تعلم اللغة العربية في هذا الفصل، وهما: المشكلات اللغوية مثل: (أ) قلة فهم الطلاب للدروس التي قدمها المعلم، (ب) نقصان قدرة الطلاب في الكتابة العربية ، (ج) قلة حفظ الطلاب لمفردات العربية. والمشكلات غير اللغوية مثل: (أ) قلة دافعية الطلاب في تعلم اللغة العربية، (ب) نقصان الكتب المقررة باللغة العربية لدي الطلاب، وغيرها. استنادًا إلى نتائج البحث، يقترح الباحث للأطراف المعنية بالطلاب، وخاصة معلمي اللغة العربية، ينبغي أن يولوا اهتمامًا لجدية تعلم الطلاب وأن يقدموا لهم دافعية مستمرة في تعلم اللغة العربية حتى يكون لديهم النشاط لمواصلة تعلم اللغة العربية والقدرة على التواصل بها في حياتهم اليومية. وأسهمت هذه الدراسة بشكل طبيعي في نشر المعرفة بأن هناك مشكلات في تعلم اللغة العربية من جانب الطلاب ليست مشكلات لغوية فحسب، بل إنما مشكلات غير لغوية أيضًا.